Isolation and selection of potential probiotic lactic acid bacteria from Opuntia ficus-indica fruits that grow in Northwest Argentina - Veron Ponce, Hernan Esteban (2017)
Lactic acid fermentation of cactus fruit (Opuntia ficus-indica) juice constitutes an important biotechnology process for its preservation. The present study shows the isolation and selection of potential probiotic autochthonous strains for the preparation of a fermented cactus fruit juice. 17 strains of lactic acid bacteria were isolated from O. ficus-indica fruits that grow in arid regions from Argentina. Isolates were screened for probiotic traits such as gastrointestinal stress tolerance, cell surface properties and antimicrobial activity, and also for their effects on functional properties of fermented juices. Among 17 isolates, 4 showed singular properties to be used as starters in cactus pear juice fermentation. These strains were identified as Lactobacillus plantarum S-811, L. plantarum S-TF2, Fructobacillus fructosus S-22, and F. fructosus S-TF7. The selected strains have potential for their use in the fermentation of cactus pear juice contributing to its preservation and the conservation of its health-promoting features.